Measurement of direct photon pair production cross sections in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; et al. (Elsevier B.V., 2010)
We present a measurement of direct photon pair production cross sections using 4.2 fb(-1) of data collected with the do detector at the Fermilab Tevatron p (p) over bar Collider. We measure single differential cross sections as a function of the diphoton mass, the transverse momentum of the diphoton system, the azimuthal angle between the photons, and the polar scattering angle of the photons. In addition, we measure double differential cross sections considering the last three kinematic variables in three diphoton mass bins. The results are compared with different perturbative QCD predictions and event generators. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Diphoton; Cross section; DPP; Differential; DO; Tevatron